The target trial framework in global health research: barriers and opportunities - Al-kassab-Córdova, Ali (2025)
A randomised trial is the best way to make causal inferences when evaluating the effectiveness and safety of health interventions in global health research. Trials, however, are inherently expensive, unfeasible in many scenarios, and may raise ethical issues. In these scenarios, we must turn to analyses of observational data to learn what works. The target trial framework provides an organising principle for the design of observational studies that can lead to clinically interpretable results and analytic approaches that can reduce common biases. In this analysis, we describe the global distribution of data sources used in applications of the target trial framework and discuss barriers to its increased use in global health research, such as limited access to high-quality observational data. We then suggest a cost-effective solution of incorporating the collection of additional high-quality observational data into the implementation of large randomised trials in low- and middle-income countries. We found that the target trial framework is underutilised in observational studies conducted in most low- and middle-income countries. The main barriers are little available data and few trained researchers, which can be overcome by incorporating high-quality observational data collection into the data collection phase of large randomised trials, and by introducing small adjustments to the teaching curriculum.